Development and validation of a HyperChem-integrated project-based e-module on molecular shapes to enhance students’ digital literacy - Meliza, Meliza; Sucahyo, Eko; Hasibuan, Mutiah Novriani; Siregar, Sevvida (Universitas Jambi, Indonesia, 2026)
This study aimed to develop and validate a project-based e-module on molecular shapes integrated with HyperChem computational media to enhance students’ digital literacy skills. The study employed the Plomp development model, which is a framework for educational design that consists of preliminary research, prototyping, and assessment phases. The participants were undergraduates enrolled in a basic chemistry course. Data were collected through expert validation sheets, practical questionnaires, and student learning activities. The validity of the e-module was assessed using Aiken’s V, and practicality was assessed using descriptive percentages. The results showed that the average Aiken’s V value was 0.89, indicating high validity. The practicality test conducted with students yielded an average score of 87.84%, indicating that it was very practical. These findings indicate that the developed HyperChem-integrated project-based e-module is valid and practical for supporting chemistry learning, particularly in improving students’ digital literacy and understanding of molecular shapes.